Pemenuhan Hak Anak yang Menikah Pada Usia Dini di Desa Datar Kecamatan Dayeuhluhur Kabupaten Cilacap - Amalia Syahidah, Jihan (Fakultas Syariah IAIN Madura, 2024)
This article focuses on studies regarding including child rights for married couples at an early age by analyzing them based on Law Number 26 of 2019 concerning marriage, Law No. 35 of 2014 concerning child protection, Law Number 39 of 2009 concerning Human Rights, Islamic views and is linked to government policies to guarantee children's rights. This research is a qualitative descriptive study, primary data was obtained from observation, in-depth interviews with several informants, and documentation. The focus of the problem in the article is on how to provide rights for children who marry at an early age in Datar Village, Dayeuhluhur District, and how the government participates in realizing the rights of children who marry at an early age. This article shows that children's rights in Datar village have not been implemented properly due to several obstacles, namely psychological, cultural, and regulatory barriers. The role of the Cilacap Regency government is realized by making regional regulation Number 2 of 2022 concerning KLA or Child-Friendly Regency and the formation of a KLA task force to create a Cilacap Regency that protects and supports educating children's rights, especially for those who are married at an early age.